2019
DOI: 10.7717/peerj.6960
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic analyses and virulence characterization ofGlaesserella parasuisisolates from Taiwan

Abstract: Background Glaesserella (Haemophilus) parasuis (G. parasuis) causes severe economic losses in the swine industry. Multiple G. parasuis strains can exist in single animals. Typing techniques are required for identifying G. parasuis isolates. Different strains within a serovar display varying virulence. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) can assess the heterogeneity. The group 1 virulence-associated trimeric autotransporters (vtaA) gene is an indicator of virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Haemophilus parasuis, or Glaesserella parasuis (G. parasuis) according to the new taxonomic reclassification, is normally a benign swine commensal in upper respiratory tract but may cause severe vascular lesions and multiorgan dysfunction, eliciting serious economic losses annually worldwide [46,47]. Commercial bacterins are often used to vaccinate swine against H. parasuis, but the deficiency in crossreactivity makes sole-serotype inactivated vaccine an ineffective means of protection against this disease [48].…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilus parasuis, or Glaesserella parasuis (G. parasuis) according to the new taxonomic reclassification, is normally a benign swine commensal in upper respiratory tract but may cause severe vascular lesions and multiorgan dysfunction, eliciting serious economic losses annually worldwide [46,47]. Commercial bacterins are often used to vaccinate swine against H. parasuis, but the deficiency in crossreactivity makes sole-serotype inactivated vaccine an ineffective means of protection against this disease [48].…”
Section: Discussionmentioning
confidence: 99%
“…G. parasuis is usually a benign swine commensal in the upper respiratory tract but may cause severe multiorgan dysfunction and vascular lesions when the host immunity drops [ 27 ]. Commercial bacterins are usually used to vaccinate swine against G. parasuis , but the lack of cross-reactivity makes sole-serotype inactivated vaccine an invalid means of protection against this disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serotyping is the most commonly used subtyping method, and is traditionally considered to be associated with virulence, but increasing evidence indicated that serovar is a poor proxy for virulence ( 14 , 40 , 41 ). To resolve this problem, such as genome-wide association study (GWAS), enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) ( 42 ), multiplex PCR (mPCR) ( 43 ) and multilocus variable number of tandem repeats analysis (MLVA) ( 44 ), have been used to differentiate G. parasuis strains and predicte virulence-associated genes. Although several studies have identified putative virulence-associated genes, their role in pathogenesis has not been demonstrated ( 45 48 ).…”
Section: Discussionmentioning
confidence: 99%